2017
DOI: 10.1080/09273948.2017.1306085
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella TyphiAssociated Endogenous Endophthalmitis: A Case Report and a Review of Literature

Abstract: Endogenous endophthalmitis can be one of the rare sequelae of enteric fever and may present in the acute and relapsing phases and often times have a rapidly fulminant course with poor visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Salmonella-associated endophthalmitis is associated with a poor outcome, with all reported cases progressing to complete vision loss, and many cases requiring enucleation or evisceration. 15,16 In human medicine, studies have shown that the repeated use of topical antibiotics significantly alters the composition of the normal ocular flora and potentially allows for the colonization of other opportunistic and more virulent pathogens. 17 Following phacoemulsification, the dog was treated with topical ofloxacin due to its broad spectrum coverage and its ability to penetrate an intact corneal epithelial layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella-associated endophthalmitis is associated with a poor outcome, with all reported cases progressing to complete vision loss, and many cases requiring enucleation or evisceration. 15,16 In human medicine, studies have shown that the repeated use of topical antibiotics significantly alters the composition of the normal ocular flora and potentially allows for the colonization of other opportunistic and more virulent pathogens. 17 Following phacoemulsification, the dog was treated with topical ofloxacin due to its broad spectrum coverage and its ability to penetrate an intact corneal epithelial layer.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous endophthalmitis is a rarely reported complication of Salmonella infections in humans. Salmonella ‐associated endophthalmitis is associated with a poor outcome, with all reported cases progressing to complete vision loss, and many cases requiring enucleation or evisceration 15,16 . In human medicine, studies have shown that the repeated use of topical antibiotics significantly alters the composition of the normal ocular flora and potentially allows for the colonization of other opportunistic and more virulent pathogens 17 .…”
Section: Discussionmentioning
confidence: 99%
“…74 Endogenous endophthalmitis is a rare complication of salmonella infections occurring in immunocompromised patients. 75 Patients with bilateral confluent retinitis had significantly high Widal titres. 76 Bilateral retinitis following typhoid fever was also reported.…”
Section: Bacterial Typhoidmentioning
confidence: 98%
“…16,77 Multifocal choroiditis following simultaneous hepatitis A, typhoid fever, and yellow fever vaccination is an inflammatory disease characterised by multiple, small, yellow fundus lesions and vitreous inflammation which is because of the involvement of the eye which may be a result of direct invasion or immune-mediated phenomenon. 75…”
Section: Bacterial Typhoidmentioning
confidence: 99%
“…1 Its incidence is relatively low: Endogenous sources account for 5% to 15% of all endophthalmitis cases. 1,2 EE is caused by the spread of bacteria/fungi from blood to the eyeball. Pathogens penetrate the blood-eye barrier, invade the eye, and cause severe vision damage; patients with this condition show poor prognosis.…”
mentioning
confidence: 99%